2020
DOI: 10.18553/jmcp.2020.26.7.910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pharmacist-Led Intervention to Improve Statin Use in Persons with Diabetes

Abstract: BACKGROUND: The Statin Use in Persons with Diabetes (SUPD) measure, developed and endorsed by the Pharmacy Quality Alliance and National Quality Forum, has been adopted by the Centers for Medicare & Medicaid Services as part of the star rating measure set. It was added as a display measure in 2015 and, as of 2019, has become a star measure. Clinical pharmacy specialists (CPS) embedded in the patient-centered medical home (PCMH) are well positioned to review and recommend statin therapy for patients with diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A prospective trial by Anderson et al [ 19 ] assessed the effectiveness of clinical pharmacists embedded within several patient centered medical home (PCMH) clinics to improve the statin use in persons with DM (SUPD) measure among a managed care population. A list of patients was received aged 40–75 with at least two medication fills for DM with no statin prescription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective trial by Anderson et al [ 19 ] assessed the effectiveness of clinical pharmacists embedded within several patient centered medical home (PCMH) clinics to improve the statin use in persons with DM (SUPD) measure among a managed care population. A list of patients was received aged 40–75 with at least two medication fills for DM with no statin prescription.…”
Section: Resultsmentioning
confidence: 99%
“…Two trials evaluated two different types of pharmacy interventions, direct-patient outreach versus coordinating with providers about statin eligibility prior to an upcoming patient appointment [ 17 , 18 ] each reporting a statistically greater proportion of patients prescribed statin therapy with the provider coordination intervention vs. the direct-patient outreach intervention. However, Anderson et al [ 19 ] reported somewhat similar success with a direct-patient outreach intervention which allowed pharmacists to prescribe statins in consenting patients via a CDTM protocol. In each of these studies, pharmacists were to some degree already implemented in these clinical sites, suggesting a positive provider-pharmacist relationship may have already been formed.…”
Section: Discussionmentioning
confidence: 99%
“…System-wide prospective interventions by clinical pharmacists have been shown to increase guideline-directed statin therapy for indications such as diabetes and ASCVD. 25 29 These approaches are Class I recommendations in the 2018 AHA/ACC/Multisociety cholesterol guideline for implementation of evidence-based statin therapy. 7 A similar combination of approaches including chart review, reporting systems, and prospective recommendations and/or direct prescribing by a clinical pharmacist or health promotion team has the potential to be utilized in the PLWH population.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend that all patients be started on a statin 1 to 2 weeks following heart transplant regardless of cholesterol levels , making statin therapy a cornerstone of CAV prevention 1 . Despite their known benefits, statin intolerance in HTRs is commonly reported, 7 often leading to discontinuation of therapy. Similar to the nontransplant literature in hypertension management, pharmacist integration has demonstrated improved statin utilization among nontransplant recipients, 7 and pharmacists are well‐poised to educate, personalize, and re‐challenge therapy as appropriate to improve statin compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their known benefits, statin intolerance in HTRs is commonly reported, 7 often leading to discontinuation of therapy. Similar to the nontransplant literature in hypertension management, pharmacist integration has demonstrated improved statin utilization among nontransplant recipients, 7 and pharmacists are well‐poised to educate, personalize, and re‐challenge therapy as appropriate to improve statin compliance.…”
Section: Discussionmentioning
confidence: 99%